Perbandingan Sistem Kendali Ar-Drone Menggunakan Leap Motion Pada Node Js dan Labview - Hendra Hendra; Gembong Edhi Setyawan; Wijaya Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Quadcopter is one of Unmanned Aerial Vehicle which is used such a field of defense, agriculture and other fields. Quadcopter is a flying machine that works with the remote control that controled by the pilot using the law of aerodynamics to lift himself or other object. The majority of quadcopter controls still using a remote controller in the form of a joystick or using android based applications. Whereas a simple movement in quadcopter control can help the pilot to control the quadcopter properly.The innovations from Natural User Interfaces (NUI) is to use natural human language such as voice, movement, or view to communicate with quadcopter. In this research will created a control that using innovation from NUI to control quadcopter in the form of simple hand movement of the user. User's hand movement will be detected using leap motion. Leap motion is a device where optical sensor and infrared light detecting the movements of a hand. Leap motion and quadcopter are programmed using javascript and Labview. After testing the performance of its precision the movement and speed, the result percentage of motion accuracy is 100%. At the resulst speed that generated by quadcopter to Pitch, Roll, yaw, gaz moves are directly proportional with value obtained from user movement, When the input from the user gets larger, the quadcopter speed will getting faster and otherwise. The result of delay response test that obtained from the user moving his hands using node.js is 0.258 seconds while the result of delay response system that performed using Labview is 0.131 seconds. Based on its resulst that using Labview programming to control the quadcopter is more responsive than using programming languages javascript.